Panelists' acceptance of ice cream with the addition of snakehead fish albumin extracts (Ophiocephalus striatus) - Dewi Kartikasari; Agustiana Agustiana; Arianto Arianto (Journal of Agritechnology and Food Processing, 2024)
The characteristics of albumin extract with a distinct fish aroma are less preferred by some people. To improve the acceptance of fish albumin extract, it is added to carrier foods such as ice cream. This study aims to evaluate the panelists' acceptance of ice cream with the addition of snakehead fish albumin extract. The research stages are: (1) extraction of snakehead fish albumin and (2) ice cream processing with the addition of snakehead fish albumin extract at concentrations of 0%, 2%, 4%, and 6% of the total water content (300 ml). A hedonic test was analyzed using the sign test to determine the level of preference for the ice cream. The results showed that the addition of snakehead fish albumin extract significantly affected the color and aroma, but did not significantly affect the texture and taste of the ice cream. The conclusion indicates that ice cream with up to 6% snakehead fish albumin extract can be accepted by the panelists, with color (5.2), texture (5.8), aroma (5.9), and taste (6.2), all meeting the "like" criteria. The suggestion for future research is to investigate the chemical quality of ice cream with the addition of snakehead fish albumin extract.